Repeated positron emission tomography tracing neutrophil elastase in a porcine intensive-care sepsis model - Frida Wilske; Olof Eriksson; Rose-Marie Amini; Sergio Estrada; Helena Janols; Amina Khalil; Anders Larsson; Miklós Lipcsey; Sara Mangsbo; Jonathan Sigfridsson; Jan Sjölin; Paul Skorup; et al. (Intensive Care Medicine Experimental)
Abstract Background Neutrophil granulocytes are important parts of the defence against bacterial infections. Their action is a two-edged sword, the mediators killing the intruding bacteria are at the same time causing tissue damage. Neutrophil activation is part of the dysregulated immune response to infection defining sepsis and neutrophil elastase is one of the powerful proteases causing both effects and damage. Inhibition of neutrophil elastase has been tried in sepsis and ARDS, so far with inconclusive results. Methods We used positron emission tomography (PET) combined with computed tomography (CT) and the selective and specific neutrophil elastase inhibitor PET-tracer [11C]GW457427 ([11C]NES), in an intensive care unit porcine Escherichia coli sepsis model with the primary aim to visualise the biodistribution of neutrophil elastase in the initial acute phase of the septic reaction. Repeated PET–CT investigations were performed before and after induction of sepsis. Results At baseline [11C]NES uptake was found in the bone marrow, spleen and liver. The uptake in the bone marrow was markedly increased two hours into the sepsis, whereas in spleen and liver the uptake was not as markedly changed compared to baseline. At 4 h after the sepsis induction [11C]NES in the bone marrow decreased while the uptake increased in the spleen, liver and lungs. Conclusion The neutrophil elastase PET-tracer [11C]NES is a novel and unique instrument to study the acute innate neutrophil immune response in sepsis and associated vital organ failure. We here present images and quantitative data of the neutrophil elastase distribution the first hours of acute experimental sepsis. Surprisingly, a pronounced increase of neutrophil elastase was found in the bone marrow 2 h into the sepsis reaction followed at 4 h by increase in the liver, spleen and lungs and a concomitant reduction of the tracer uptake in bone marrow.